1986
DOI: 10.1037/0022-0167.33.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and psychotherapy with Asian-Americans: Review of the literature.

Abstract: This article is divided into three sections. The first section concerns the diagnosis and assessment of Asian-Americans and covers the following issues: (a) symptom expression, (b) therapist bias, (c) problems with the use of interpreters, and (d) problems with the use of clinical and personality tests. The second section, on counseling and psychotherapy, is divided into three subsections: (a) client variables, (b) therapist variables, and (c) counseling process and outcome. The subsection on client variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
261
5

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(276 citation statements)
references
References 107 publications
(128 reference statements)
10
261
5
Order By: Relevance
“…Some researchers have suggested that for Asians, the underutilization of professional psychological help has included lack of knowledge or cultural stigmas (Leong, 1986;Leong & Lau, 2001;Mau & Jepsen, 1988;Yeh, 2002). The present study of adolescent students in Singapore supports such work, since the data indicate that lack of knowledge is one of the reasons why adolescents underutilize formal sources of help.…”
Section: Resultssupporting
confidence: 65%
“…Some researchers have suggested that for Asians, the underutilization of professional psychological help has included lack of knowledge or cultural stigmas (Leong, 1986;Leong & Lau, 2001;Mau & Jepsen, 1988;Yeh, 2002). The present study of adolescent students in Singapore supports such work, since the data indicate that lack of knowledge is one of the reasons why adolescents underutilize formal sources of help.…”
Section: Resultssupporting
confidence: 65%
“…Leong, Chang, and Lee (2007) noticed that research on specific psychological issues has become a trend in recent research on acculturation. Harwood (1994) suggested researchers redefine acculturation by taking into consideration the impact of globalization, which has blended the borders of different cultures.…”
Section: Acculturation Measurementsmentioning
confidence: 99%
“…Several studies (Chang, 1996;Huang et al, 2004;Leong, 1986) report that some members of Asian American populations are less assertive and more submissive than those in non-Asian American populations. In particular, Huang et al note that this demeanor, consistent with Asian values, may result from the struggle for harmony and, consequently, result in discouraging individualism.…”
Section: Confucian Culturementioning
confidence: 99%